El Dietari de Jaume Ramon Vila, una obra fragmentada. - MARTORELL, ARANTXA LLÀCER (Scripta, 2016)
The study of a work from a copy carries a risk that is increased if we work with a altered copy by the copyist. In the case of Jaume Ramon Vila' Diary, preserved from a partial copy, carried out from a previous copy, we must analyzing the structure, in order to try to clarify how far we have received the work as it was intended by its author, and what changes it has undergone in the text and content. In this article we provide the irst study that approaches the researchers know the Diary of Jaume Ramon Vila through an intense activity of reorganization and recovery of news.